Implementasi Corporate Social Responsibility PT. Riau Andalan Pulp and Paper Terhadap Masyarakat di Kabupaten Pelalawan - Shandy Utama, Andrew (Program Studi Ilmu Hukum Universitas Maritim Raja Ali Haji, 2018)
Corporate Social Responsibility (CSR) is an inherent responsibility of the company to keep creating harmonious, balanced, and harmonious relationships with the environment, values, norms and culture of the community. Corporate Social Responsibility is basically a derivation of business ethics, which can bridge the interests of the company with the needs of the community, both directly and indirectly affected by the companys operations. The problem is how is the regulation of Corporate Social Responsibility in the legal system in Indonesia? How is the implementation of Corporate Social Responsibility of PT Riau Andalan Pulp and Paper on improving peoples welfare in Pelalawan Regency? The method used in this research is sociological law research using approach to the implementation of legislation, namely Law Number 40 Year 2007 and Riau Province Regional Regulation No. 6 of 2012, on the implementation of Corporate Social Responsibiity PT Riau Andalan Pulp and Paper. The result of this research is that Corporate Social Responsibility which initially is only the moral responsibility for the company to the society residing in the vicinity of the companys location is now transformed into legal responsibility in the form of obligation for the company to improve the prosperity of the people who live around the company location according to Law Number 40 of 2007 which is implemented in Riau Province with Riau Province Regional Regulation Number 6 of 2012. PT Riau Andalan Pulp and Paper has implemented Corporate Social Responsibility to improve community welfare in Pelalawan Regency in accordance with the provisions regulated by law - the prevailing law.